Development of Santriwati Skills in Arabic through the Darul Lughoh Program at Islamic Boarding Schools in Lamongan Regency - Reni Prasetyawati; Khizanatul Hikmah (Indonesian Journal of Islamic Studies, 2022)
This study aims to balance the skills of female students in Arabic, so Pondok Al-Mizan Muhammadiyah Lamongan makes a Darul Lughoh program. To achieve the expected goals, a good process is needed in language development institutions. This research is a qualitative descriptive study, the techniques used to collect data are observation techniques, unstructured interviews and documentation. And in this study using data analysis techniques developed by Miles and Huberman, that the activities in data analysis are data reduction, data presentation, and conclusion drawing. The results of the study found that, 1) the planning for the development of the Arabic language of female students through the darul lughoh program at the Al-Mizan Muhammadiyah Lamongan was arranged systematically, including: Formulating goals and objectives, determining programs and times, and determining strategies and policies. 2) Implementation of the development of female students' skills in intensive Arabic classes, namely One Week One Language and the program is aimed at selected students from grades 7 MTS and 10 MA. The programs include: Ilqoul Mufrodat, Islahul Lughoh, Muhadatsah, Muhadloroh bilingual, reading motivation, miss language and out door language classes. 3) Assessment of the development of female students' skills in Arabic is carried out formally such as written exams and informally in the form of accountability reports after the implementation of activities.